2015
DOI: 10.1038/srep15309
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Whole genome and transcriptome sequencing of matched primary and peritoneal metastatic gastric carcinoma

Abstract: Gastric cancer is one of the most aggressive cancers and is the second leading cause of cancer death worldwide. Approximately 40% of global gastric cancer cases occur in China, with peritoneal metastasis being the prevalent form of recurrence and metastasis in advanced disease. Currently, there are limited clinical approaches for predicting and treatment of peritoneal metastasis, resulting in a 6-month average survival time. By comprehensive genome analysis will uncover the pathogenesis of peritoneal metastasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…These processes provide intermediates for several metabolic pathways to enhance cell growth, including cancer proliferation. The coiled-coil domain-containing protein 178 (CCDC178) is an 867 amino acid polypeptide that is mutated in several human cancers including gastric cancer (168) and HCC (169). CCDC178 was reported to be overexpressed in HCC and promoted metastasis by mediating anoikis resistance via activation of the ERK/MAPK signaling pathway (24).…”
Section: Protein Metabolismmentioning
confidence: 99%
“…These processes provide intermediates for several metabolic pathways to enhance cell growth, including cancer proliferation. The coiled-coil domain-containing protein 178 (CCDC178) is an 867 amino acid polypeptide that is mutated in several human cancers including gastric cancer (168) and HCC (169). CCDC178 was reported to be overexpressed in HCC and promoted metastasis by mediating anoikis resistance via activation of the ERK/MAPK signaling pathway (24).…”
Section: Protein Metabolismmentioning
confidence: 99%
“…PMPCB is the mediator for the majority of mitochondrial proteins [32]. ARMC4 is a new gene that has been found in peritoneal metastatic gastric carcinoma [33]. PDE9A is expressed highly in the brain, and it is a cGMP-specific phosphodiesterase [34].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, whole-genome sequencing techniques that allowed to identify molecular subtypes in primitive gastric cancer cohorts have been applied to study the molecular signature of GC metastasis from different sites [31]. Recent evidences showed that CCNE1 amplification was found associated with liver metastasis in GC of the TP53 subtype [32] while mutations activating or inactivating specific genes were identified in peritoneal metastasis [33]. Circulating tumor DNA (ctDNA) detection is another innovative approach to analyze GC disease.…”
Section: Molecular Insight For Metastatic Lesionsmentioning
confidence: 99%